BASICS OF LIMITATION OF RIGHTS AND FREEDOMS IN THE ECONOMIC SPHERE - Абдуллаєв, Мехті Камал огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: consideration of basic economic rights and freedoms, as well as their legal restrictions. Methods: the methodological basis of the study was philosophical, ideological, general scientific and special methods. Results: the constitution of any state regulates the most important areas of activity of the country, society and the individual. Since the economy is an integral part of the life of society, the reflection of the basic principles of its regulation in the basic law of the state is no exception. In the Constitutions of many countries, the socio-economic topics received fairly complete coverage. They contain a list of the most significant economic problems requiring constitutional consolidation. Simultaneously with the consolidation of basic economic rights and freedoms, the basic laws of countries also contain the conditions under which the state can restrict them. Discussion: mechanisms of state regulation of economic activity of economic entities. Licensing is considered as a necessary measure of state regulation of the economy, which is an integral part of market relations. In the light of the above, the thesis that licensing is one of the most complex and serious mechanisms of state regulation of economic activities of economic entities and reducing licensing by switching to alternative regulatory methods should be carried out only for activities that do not pose a potential danger to the fundamentals of the constitutional system and fundamental human rights and freedoms.